The Real existence of State Islamic Religious College in the 4.0 Industrial Revolution - Supriyatno, Triyo (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
This paper aims to find the reforms needed in the State Islamic Religious College (PTKIN). Reform in PTKIN is needed to create people to become experts in their fields and to answer all the guidelines of the times. This paper explains to provide a solution for PTKIN when the Revolutionary Era 4.0 is happening lately. That can be seen when the era of 4.0 gives a hard influence on every aspect of life. It was proven when PTKIN on 4.0 Era gave a phenomenon of disruption that demanded the world of Education, the world of PTKIN to follow and face the 4.0 era in particular. PTKIN (UIN Malang and UIN Riau) is faced with unprecedented challenges and needs. Innovation system in the management of educational curricula that will be able to create competent human resources in the field of Islam and others in general. If PTKIN ignores and does not follow the development of the 4.0 era, PTKIN will be left behind. Therefore, PTKIN is expected to be able to compete and start taking concrete steps so as to produce people who will become experts in the field of Islam and others in general so that they can compete in an era of disruption. The plan is to disrupt themselves and face this 4.0 era. This study uses a qualitative description method with literature. The results of this study are that PTKIN (UIN Malang and UIN Riau) must prepare for the Revolution Era 4.0